Renewable Energy and Electricity Security : Smart Grid development prospects for Azerbaijan - Mammadli, Laman (ADA University, 2023)
This study focuses and analyzes whether the current traditional electricity system of Azerbaijan is ready to absorb and incorporate a large share of intermittent and non dispatchable renewable sources, assesses current reforms in country’s electricity sector and determines the challenges in the prospect of smart grid development. Azerbaijan has almost 200 GW of technical potential in developing renewable energy sources, however, the penetration of renewables to the current conventional grid will rise another big issue of electricity security. The development of a smart grid system is considered as a solution to renewable energy transition. The study evolves interviews with industry experts as a primary source to get the complete picture of the existing electricity system and comparative analysis of the international best-case scenario as a secondary. The findings show that the legislative background and grid infrastructure are far behind the vision of the government in the prospect of green energy transition. Current grid may integrate up to 1,5 GW of renewables, however, problems may occur even with lesser volumes. There is uncertainty arising from management of variable renewable energy sources within existing electric system which may bring to high number of power shortages in Azerbaijan upon its integration.
Keywords: Electric power systems -- Azerbaijan; Renewable energy sources -- Integration; Smart power grids -- Development; Public and International Affairs